Gender equality promotes development: the World Bank's gender action plan - Claudia Müller (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Gender equality is a human right. This alone is reason enough for development assistance to consider the issue. In addition, there are a number of strong economic arguments for doing so. As an example, numerous studies have shown that countries with high levels of gender equality record higher rates of economic growth than countries with low levels of gender equality. Equal opportunities for women and men are therefore critical for growth and development. It is for this reason that the World Bank, which has the mandate to promote economic development and reduce poverty, takes steps to ensure that its projects and programs incorporate gender equality components. This is true in particular for the time since 2002, when the Bank adopted its first Gender Mainstreaming Strategy. However, for a variety of reaons, the Bank still does not consider gender aspects in a systematic manner (“mainstream”) but on a caseby-case basis. In order to change this, the World Bank and donors created the Gender Action Plan (GAP). The plan, adopted for the period up to 2010, is financed from the Bank's budget (US 12 million) and donor contributions (US 48 million so far). The GAP funds support gender-specific research and project work, specifically in operational areas in which it has proven particularly difficult to consider gender aspects even though the potential benefits of doing so are large. This holds true for infrastructure, agriculture, the private sector, and financial markets. A first preliminary assessment shows that the GAP has surpassed all expectations in directing the attention of the Bank's staff, management, and executive directors to gender issues. It is particularly noteworthy that World Bank President Robert Zoellick has publicly committed the Bank to reaching concrete gender-specific targets. Despite these activities it remains questionable whether the GAP will be able to effectively change the way the Bank does its business in the long run. In order for this to happen, the Bank needs to follow up on the plan by making more funds of its own available for gender studies and by improving compliance with its internal gender policies. It is up to the donors to insist that these demands are met.
Keywords: 330